Poznawcze hybrydy i hybrydowe qualia - Robert Poczobut (Analiza i Egzystencja)
The aim of this article is to analyze selected theoretical issues concerning perceptual systems in which hybrid qualia arise. By “hybrid qualia”, I mean subjective sensory experiences generated in technologically modified perceptual systems. In the first section, I propose an original perspective on the relationships between hybrid systems, extended systems, and cyborgs. In the second section, I discuss examples of auditory, visual, and tactile hybrid qualia in technologically modified perceptual systems. In the third section, I analyze unconventional hybrid qualia in the context of research on sensory substitution, sensory enhancement, and sensory supplementation. At the end of the article, I formulate philosophical conclusions and outline prospects for further research.